Artificial Intelligence and Inequality: A Legal Aspect - A. I. Rybin; E. O. Chashhukhin (Теоретическая и прикладная юриспруденция)
The purpose of this article is to analyze the impact of artificial intelligence (hereinafter also referred to as AI) on social inequality. It is evident that AI not only brings about advantages but also serves as a means of infringing upon human rights, exacerbating social stratification at both the level of individual societies and on a global scale. Through the application of formal legal and comparative legal methodologies, it becomes apparent that the current practices of utilizing AI in various legal domains often fall short of achieving the intended objectives, sometimes even serving as a catalyst for discrimination and the perpetuation of social inequality. The paper underscores the active engagement of scholars and practitioners in addressing social inequality and other challenges associated with AI through the lens of AI ethics. The concept of AI ethics is explored, along with a critical analysis of ethical frameworks adopted by several technology companies operating in the field of artificial intelligence. It has been demonstrated that the primary cause of the emergence of social disparity in the realm of AI is not a dearth of ethical tenets in AI-driven algorithms, but rather a lack of adequate formalization of these ethical principles themselves into machine-readable language. It has been shown that the legal regulations in this domain, typically, are advisory in nature and emanate from corporations rather than from state institutions.